2011
DOI: 10.1111/j.1540-8175.2011.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Longitudinal Strain Predict Left Ventricular Remodeling after Myocardial Infarction?

Abstract: Our study has shown that LV longitudinal strain assessed by STI is an independent predictor of LV remodeling after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…As shown in previous studies, the systolic longitudinal strain (cut-off value at À11.6%) is an independent determinant of LV remodeling [22]. In our study, the systolic longitudinal strain and strain rate were decreased, but did not differ between the groups, while a lowered late diastolic longitudinal strain ratewhich correlated with fT3 -was observed on the first day.…”
Section: Discussionsupporting
confidence: 46%
“…As shown in previous studies, the systolic longitudinal strain (cut-off value at À11.6%) is an independent determinant of LV remodeling [22]. In our study, the systolic longitudinal strain and strain rate were decreased, but did not differ between the groups, while a lowered late diastolic longitudinal strain ratewhich correlated with fT3 -was observed on the first day.…”
Section: Discussionsupporting
confidence: 46%
“…Studies involving modern era patients with STEMI, which have demonstrated an association between LVGLS and LV remodeling, are limited by small numbers, variable LV remodeling definitions, and shorter follow-up periods. 27,28 The current evaluation considerably expands on previous studies by relating baseline LVGLS measurement in a large cohort of contemporary STEMI patients to accepted echocardiographic outcomes on systematic 3-and 6-month follow-up. Patients with LVGLS >−15% were significantly more likely to display pathological LV dilatation at both 3 and 6 months after STEMI.…”
Section: Lvgls and LV Remodelingmentioning
confidence: 85%
“…The diagnostic reliability of longitudinal strain is still under evaluation and it has been reported as a novel sensitive diagnostic echocardiographic parameter in some studies, while showing no exceptional importance in the others. 18,19,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…17 All other echocardiographic dimensions, severity of mitral regurgitation, assessment of regional contraction and evaluation, and longitudinal strain of LV assessed by speckle-tracking imaging were evaluated as described previously. 18 LV remodelling was defined as a ≥20% increase in LV end-diastolic volume (LVEDV) at four-month follow-up compared with the baseline, respectively. 19 …”
Section: Echocardiographymentioning
confidence: 99%